Spatial Statistic Analysis of Earthquakes in Aceh Province Year 1921-2014: Cluster Seismicity - Muzailin Affan; Muhammad Syukri; Linda Wahyuna; Hizir Sofyan (Graduate Program of Syiah Kuala University, 2016)
The purpose of this study is to apply the analysis of spatial patterns of earthquakes in the province of Aceh by detecting clusters and looking for spatial patterns locally and globally during the period 1921-2014 using GIS (Geographic Information System). The selected techniques are Average Nearest Neighbor, Moran Global Index, the Getis-Ord General G, Anselin Local Moran Index, the Getis-Ord Gi*, and Kernel Density Estimation. Each technique is implemented using GIS so that calculations can be done efficiently and quickly. The results of this study indicate that (1) The techniques can detect clusters of dots on the spatial pattern of earthquakes; (2) Both globally and locally, it shows that earthquakes clustered in the southwestern heading to the northern part of the province; (3) An earthquake with a greater magnitude generally concentrated in the district of Simeulue, the western part of Aceh Besar and northwest of Sabang